Aerobic endurance levels as model control tools for individual prototypical training progres among algerian soccer players - Mohammed Zerf, Mime Mokhtar, Mohammed Hadjar Kherfane, Belkadi Adel, Wahib Beboucha (Journal of Kinesiology and Exercise Sciences, 2021)
Introduction. Exercise protocols applied to effectively reduce body fat among overweight individuals are required to improve aerobic fitness obligatory for any sports practice. Aim. In this study, the impact of maximal oxygen consumption VO2max levels was assessed regarding formative recommendations as an individual control tool used in the training progress of Algerian soccer players Materials and Methods. The study comprised 148 well-trained, first division soccer players below the age of 18. The players were evaluated using the Yo-Yo test as a valid field test to evaluate both physiological functions (aerobic and anaerobic), allied to simulate soccer-specific player performance levels. Anthropometric characteristics, such as Body mass index BMI, Body Fat Percentage BFP and weight loss were also assessed, based on bioelectrical impedance analysis (BIA) technology. This was reflected in similarities as valuable anthropometric measurements to control changes in the players’ body, relative to maximal oxygen consumption during dynamic exercise with large muscle groups. Performance in this case was assessed from the formula of the Yo-Yo test to validate the hypothesis that VO2max 60 ml/kg/min is the minimum fitness challenge for male soccer players to play at a European elite level. Via soccer match analysis, it was noted that an average oxygen uptake of approximately70% of maximal oxygen uptake (VO2max) during a match for elite soccer players is required. The study groups were divided into 2 samples to carry out the research protocol (below and above the VO2max ± 60 ml/kg/min threshold). Results and Conclusions. Based on statistics applied and the strategy used, our results revealed the VO2max of up to 60 ml/kg/min was an optimal preventive weight loss programme for the players, resulting not only from the advantageous Algerian players’ physiological training status levels, but also through their athletic body and performance.
Keywords: Body mass, lossVO2max, levels physiological ,profile soccer, players